Uncle John's city garden - Ford, Bernette G. (Holiday House, 2022)
While visiting her uncle John in the city for the summer, an African American girl, L'il Sissy, her siblings, and uncle transform an empty lot into a vegetable garden. Includes recipe for succotash.